When agriculture rules over the territory: Drystone walls - Marçal Gonçalves, Marta (2022)
The objectives of this paper are mainly the dissemination of knowledge about drystone walls, a “minor heritage”, and the awareness of its importance in the territory characterization. These objectives are achieved when this theme is disclosed and explained. Heritage is protected and appreciated only if it is understood. The expected practical impact is essentially related to the recognition of this type of heritage. The main methodology consists of bibliographical and iconography collection, field surveys and exchange of ideas with the local people. The approach is made from the point of view of how the practiced agriculture characterizes the territory, not only its structure, because is also necessary to know the local typologies of drystone walls to allow to characterize them. Some characteristics of drystone walls were discovered in this investigation, which are directly related to the territory where they are inserted. The following limitations were found: the gradual replacement of drystone walls with masonry walls; changes in the type of agriculture; the difficulty of finding masters who have the know-how about drystone walls; the recognition of this heritage by the local population; and the gradual local population diminution. Practical implications are an improved sense of belonging and identity as the knowledge and appreciation of this heritage increases the pride of the population which was verified in the field surveys. The originality of this paper is the object of study, the Parish of Cernache do Bonjardim, Portugal, since there are very few works about it, also with added value to the dissemination of this type of heritage and its potential exploitation and protection by local population. It is possible to renew theterritory of these walls and use it for touristic, educational and cultural purposes, encouraging the local economy.